On the estimation of the hedging of the asset price involving the asian option - T. Dumrongpokaphan (2018)
© 2016 Pushpa Publishing House. All rights reserved. In this paper, we study the hedging, particularly, the delta-hedging, the gamma-hedging and the theta-hedging of the asset price involving the Asian option. Actually, we know that the Asian option has no closed form. So, in this paper, we can estimate such closed form solution from the partial differential equation involving such Asian option. We obtain the new result which is interesting and may be useful in the research area of financial mathematics.